2008
DOI: 10.1503/cmaj.071241
|View full text |Cite
|
Sign up to set email alerts
|

Intentions of smokers to use free nicotine replacement therapy

Abstract: CMAJ 2008;179(2):145-6Une version française de ce résumé est disponible à l'adresse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
1
9
0
1
Order By: Relevance
“…In the present study, cutting down smoking before surgery was common and, anecdotally, many erroneously believed this would be enough to reduce peri‐operative risk. The lower rate of offer acceptance in those smoking less was consistent with this risk perception, which is an effect that has been described previously .…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, cutting down smoking before surgery was common and, anecdotally, many erroneously believed this would be enough to reduce peri‐operative risk. The lower rate of offer acceptance in those smoking less was consistent with this risk perception, which is an effect that has been described previously .…”
Section: Discussionsupporting
confidence: 89%
“…This helps explain why a survey (6) of family physicians in Montreal, Quebec, found that only 10.5% provided 'thorough' smoking cessation counselling, and less than one-half offered adjunct support to patients. In contrast, a recent survey (7) found that more than one-half of smokers would be interested in nicotine replacement therapy if it were offered free of charge.…”
mentioning
confidence: 89%
“…In addition, our previous research has indicated that prior use of NRT is actually positively related to current interest in using NRT again [10]. Thus, one of the secondary analyses of this study will test the moderating hypothesis that prior use of NRT is negatively related to future success with NRT when it is offered for free.…”
Section: Methodsmentioning
confidence: 94%
“…Research conducted in New York State found that 53% of smokers indicated that the free distribution of NRT would be most effective in motivating them to think seriously about stopping smoking [ 9 ]. A Canadian population survey similarly found that 58.9% of ≥ 10 cigarettes per day smokers expressed interest in receiving free nicotine patches and of those, almost all indicated they would use nicotine patches to quit permanently [ 10 ]. Heavier smokers were more likely than less heavy smokers to be interested in receiving free NRT.…”
Section: Introductionmentioning
confidence: 99%